Studi Kasus Asuhan Kebidanan Komprehensif pada Nyonya M di Klinik Pratama Shaqi, Sleman - Crisma Martadiana; Nining Tunggal Sri Sunarti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Comprehensive midwifery care is essential for early detection of complications and reducing maternal and infant mortality rates. In Sleman Regency, despite high access to health services, continuous monitoring remains crucial for ensuring maternal and fetal safety. Objective: To provide comprehensive midwifery care for Mrs. M at Klinik Pratama Shaqi, Sleman, from the third trimester of pregnancy through the postpartum and neonatal periods. Methods: This is a descriptive qualitative study using a case study approach based on Varney's seven-step midwifery management and SOAP documentation. Findings: During pregnancy (37 weeks 6 days), the mother experienced physiological complaints of back pain and shortness of breath, managed through posture education and pregnancy exercises. Labor proceeded normally and spontaneously on October 6, 2024, utilizing